The influence of the west African songs of Derision in the new world - van Dam, Theodore (International Library of African Music, 1954)
Jazz has an ancient and honourable tradition. Some of its elements, especially rhythm, may probably be traced back directly to West Africa. Actually West African music, in the course of its evolution, has influenced nearly all the music of the New World.
Keywords: Ethnomusicology; West Indies; Music; Blues (Music); Calypso (Music); Jazz; Africa; West Africa; India; Foreign Influences; African Music